Advances in East Asian Agricultural Origins Studies: The Pleistocene to Holocene Transition - Yu, Pei-Lin; Kazunobu, Ikeya; Zhang, Meng (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Scientific understanding about domestication and the origins of food production in East Asia is undergoing rapid change based on new data from archaeology, paleobiology, and paleoenvironmental studies. The earliest agricultural and pastoral societies emerged from the highly diverse habitats and Paleolithic cultures of East Asia. This offers an unprecedented opportunity to understand and predict variability in the tempo and mode of the Paleolithic to Neolithic transition. Advances in East Asian Agricultural Origins Studies: The Pleistocene to Holocene Transition aims to present the most advanced research from varied regions of East Asia, with the purpose of evaluating the significance of Paleolithic cultural influences on the transition to Neolithic adaptations by comparing cultural evolutionary scenarios through time and across space. The array of approaches will be multidisciplinary, featuring quantitative, qualitative, and integrated data and methodologies. Understanding the transition from foraging to Neolithic agriculture, which was among the most dramatic and influential in the history of modern Homo sapiens, has ramifications for the study of Late Quaternary growth of human populations, societal complexity, landscape use, migration, and impacts on ecosystems.